67.1k views
0 votes
Use substitution to solve the linear system of equations. y=-3x+1 y=2x-4 (-2, 1) (1, -2) (1, 2) (-1, -2)

User Dima
by
5.7k points

1 Answer

4 votes

Answer:

Solution of the equations is (1, -2).

Explanation:

Two linear equations given in the question are

y = -3x+1-------------(1)

and y = 2x-4 ------------(2)

To solve these equations by substitution method we will substitute the value of y from equation (1) to equation number (2).

-3x+1 = 2x-4

Now we add 3x on both the sides of the equation

3x-3x+1 = 3x+2x-4

1 = 5x-4

we will add 4 on both the sides

1+4 = 5x-4+4

5 = 5x

Then we divide the equation by 5

5/5 = 5x/5

x = 5/5 = 1

Now we solve the equation (1) for the value of y by putting x = 1

y = -3(1)+1 = -3+1 = (-2)

So the solution will be (1 -2).



User Jennie
by
5.3k points